From researched to centrestage - Newsome, Jennifer K. (Muzikološki zbornik, 2008)
Applied research is a key way for music researchers to respond to the research agenda of Aboriginal and Torres Strait Islander peoples. Developments at the Centre for Aboriginal Studies in Music (CASM) point to applied researchas an effective response to the call for self-determination and self-representation by Indigenous peoples in research.
Keywords: Aborigini; Australia; Avstralija; etnomuzikologija; glasba; music